2012
DOI: 10.3109/07420528.2012.702587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Time-of-Day of Hypertension Treatment on Ambulatory Blood Pressure and Clinical Characteristics of Patients With Type 2 Diabetes

Abstract: Generally, hypertensive patients ingest all their blood pressure (BP)-lowering agents in the morning. However, many published prospective trials have reported clinically meaningful morning-evening, treatment-time differences in BP-lowering efficacy, duration of action, and safety of most classes of hypertension medications, and it was recently documented that routine ingestion of ≥1 hypertension medications at bedtime, compared with ingestion of all of them upon awakening, significantly reduces cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 93 publications
0
26
0
2
Order By: Relevance
“…Finally, antagonism of the RAAS by reduction of angiotensin II formation and blockade of its receptors achieved either by a bedtime ACEI or ARB ingestion strategy is superior to any other treatment strategy for reducing risk of new-onset diabetes. Future prospective intervention trials that incorporate periodic, annually or more frequent, ABPM assessments during long-term follow-up evaluation, as done in the MAPEC study and the currently ongoing multicentre Hygia project [38,39], are necessary to confirm the reduced risk of new-onset diabetes by bedtime hypertension chronotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, antagonism of the RAAS by reduction of angiotensin II formation and blockade of its receptors achieved either by a bedtime ACEI or ARB ingestion strategy is superior to any other treatment strategy for reducing risk of new-onset diabetes. Future prospective intervention trials that incorporate periodic, annually or more frequent, ABPM assessments during long-term follow-up evaluation, as done in the MAPEC study and the currently ongoing multicentre Hygia project [38,39], are necessary to confirm the reduced risk of new-onset diabetes by bedtime hypertension chronotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…El impacto de la administración nocturna sobre la regulación de la PA parece tener un efecto clínico importante, ya que mediante el MAPA se mostró una asociación entre el patrón non-dipper nocturno y un incremento en la incidencia de eventos CV fatales y no fatales; este patrón non-dipper y la HA nocturna es altamente predominante en pacientes con DM2 128 .…”
Section: Posologíaunclassified
“…Clinical practice guidelines are unanimous on the pivotal role of angiotensinconverting enzyme inhibitors (ACEIs) and angiotensin receptors antagonists in BP lowering strategies in people with diabetes [12]. It has been suggested that compared to morning ingestion, bedtime ingestion of more than one antihypertensive drug could induce a better reduction of incident cardiovascular events in type 2 diabetes patients [13]. Perindopril is a long acting ACEI, which displays similar pharmacodynamic properties to other agents in this class.…”
Section: Introductionmentioning
confidence: 99%